VISUALIZING SUSTAINABILITY IN ACCOUNTING: INTEGRATING PHOTOGRAPHY INTO ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) REPORTING - Sugianto, Sugianto; Usman, Ernawaty; Usman, Asri; Adys, Himaya (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Sustainability accounting has expanded beyond financial metrics to include environmental, social, and governance (ESG) dimensions. However, conventional ESG reports typically dominated by numerical indicators and textual descriptions, often fail to capture the emotional, symbolic, and cultural aspects that shape stakeholder understanding and engagement. This study aimed to explore the role of photography as both a narrative and an evidentiary tool in ESG reporting. Using a qualitative visual ethnography approach, the research analysed original photographs taken in urban and community settings to represent dynamics related to ESG, such as human–nature relationships, informal governance, and collective social actions. The images were collected through field immersion and contextual observation. Findings suggested that photography can enrich ESG reporting by adding emotional depth and ethical meaning, thereby enhancing communication and stakeholder connection. This study advocates for photography as a valid and verifiable method to support more inclusive and engaging sustainability disclosures.